PHARMACOLOGICAL VERSUS PSYCHOLOGICAL TREATMENT IN ODONTOPHOBIA: THE RIGHT APPROACH - Alin Dumitru Ciubotaru; Carmen-Ecaterina Leferman; Cezar Foia; Karina Cojocaru; Bogdan Minea; Ancuța Goriuc; Daniel Cioloca (Romanian Dental Association for Education, 2023)
This review synthesizes existing literature on the comparative effectiveness of psychotherapy versus pharmacotherapy in treating odontophobia. It critically examines various studies and clinical trials that explore the outcomes of cognitive-behavioral therapy (CBT), exposure therapy, and other psychotherapeutic interventions, against pharmacological approaches like anxiolytics and sedatives in managing dental anxiety. The review assesses the efficacy, sustainability, and patient acceptability of these treatments, focusing on anxiety reduction, improvement in dental visit compliance, and long-term management of odontophobia. By integrating findings from diverse studies, this review aims to elucidate the most effective treatment modality, offering valuable guidance for clinicians in the optimized management of odontophobia.